Investigation of germination and growth characteristics in wild pistachio (Pistacia atlantica Desf.) seedlings - Ali Zeynalzadeh; Nasrin Seyedi; َAbbas Banj Shafiei (مجله جنگل ایران, 2020)
Wild Pistacia (Pistacia atlantica Desf.) from the Anacardiaceae family is drought and frost tolerant tree species. Due to the dormancy caused by physiological processes and hard and oily coating of the seeds, the reproduction and production of seedlings of this species are facing major obstacles. In this study, the effect of sowing bed, planting date and different pretreatments on wild pistachio seeds were studied in Tabriz's Elgolian nursery. In order to implement the experiment, a factorial design in a randomized complete block design with five replicates and three treatments including planting bed in three levels, planting date in two levels and pre-treatment in four levels were used. During the growing season, the diameter of the collar and seedling height were measured monthly. Also, the daily average germination, seed percentage and seed germination rate were also calculated. At the end of the growing season, biomass of the root and biomass of the stem were measured. Using gibberellic acid as a pretreatment increased seed germination percentage. In addition, the best vegetative traits were the planting bed 1 (1,1,1) and pretreatment 3 (cold, scraping and gibberellic acid) which are recommended for improving the growth and the rate of yield of wild pistachio seedlings in Elgoli nursery in Tabriz.